Model of Domestic Economic Value By Application of the Supply Chain Strategy for Case of Indonesia - Hakim, Lukmanul; Tarmizi, Nurlina; sanusi, Anuar; Herlina, Herlina; Yulianti, Dona (International Journal of Supply Chain Management, 2019)
The NED Case Indonesia Model is a study that analyzes the economic value of the time allocation of mothers working in the domestic economy in helping families based on the supply chain strategy. The core of this research is the contribution of mothers working in Palembang City, Indonesia and the supply chain strategy for their sourcing management. This study aims to look at the contribution of mothers working on the family economy and responsibilities as a mother through time allocation in the domestic sector and using the semi log regression method, cross tabulation and opportunity cost. Respondents from mothers who worked as laborers, office workers, food vendors and others, were scattered in South Sumatra, Indonesia. The analysis results, first, the economic value of the average time allocation in the domestic sector Rp. 2,497,000, - per month, above the minimum wage of Rp. 2,294,000 per month. Second, the average allocation of time mothers in the public sector to 37 hours per week and the allocation of time mothers in the domestic sector 48 hours, more than 35 hours per week. Third, using supply chain strategy to increase higher maternal income, the need for increased time allocation efficiency in the domestic sector.